2005
DOI: 10.1680/geng.2005.158.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Construction monitoring of cut and cover tunnels

Abstract: Over 700 instruments were installed to monitor the performance of the cut and cover tunnels that carry the Channel Tunnel Rail Link through Ashford. Careful monitoring confirmed design assumptions and provided a sound basis for changes to the construction sequence that accelerated the works. This paper highlights key features of the monitoring system. It describes the instruments that were installed, reviews their performance, and identifies practical issues that were addressed during the contract. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Over 700 instruments were installed during the contract, and all 14 structures were carefully monitored during construction (Holmes et al, 2005). This paper summarises the maximum wall movements and prop loads that were measured.…”
Section: Performance During Constructionmentioning
confidence: 99%
See 4 more Smart Citations
“…Over 700 instruments were installed during the contract, and all 14 structures were carefully monitored during construction (Holmes et al, 2005). This paper summarises the maximum wall movements and prop loads that were measured.…”
Section: Performance During Constructionmentioning
confidence: 99%
“…For bottom-up construction cantilever movements at the top of the wall (Roscoe, 2003) governed both deflected shape and maximum movement. Figure 11 plots the maximum wall movements at the end of excavation against retained height H. These measurements include toe movements of about 5 mm (Holmes et al, 2005) as indicated on the figure. Also shown are the linear relationships often used to estimate the movement of embedded walls (Gaba et al, 2003).…”
Section: Maximum Wall Movementsmentioning
confidence: 99%
See 3 more Smart Citations